2003
DOI: 10.1007/3-540-45105-6_54
|View full text |Cite
|
Sign up to set email alerts
|

Active Control of Thermoacoustic Instability in a Model Combustor with Neuromorphic Evolvable Hardware

Abstract: Abstract. Continuous Time Recurrent Neural Networks (CTRNNs) have previously been proposed as an enabling paradigm for evolving analog electrical circuits to serve as controllers for physical devices [6]. Currently underway is the design of a CTRNN-EH VLSI chips that combines an evolutionary algorithm and a reconfigurable analog CTRNN into a single hardware device capable of learning control laws of physical devices. One potential application of this proposed device is the control and suppression of potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In a previous research, we had demonstrated that EH techniques are better than traditional control techniques for suppressing TA instability in real time [6]. It was shown with evidence that controllers evolved using EH techniques were robust and superior in quality than the traditional controllers [8,9] for a simulated combustion chamber.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In a previous research, we had demonstrated that EH techniques are better than traditional control techniques for suppressing TA instability in real time [6]. It was shown with evidence that controllers evolved using EH techniques were robust and superior in quality than the traditional controllers [8,9] for a simulated combustion chamber.…”
Section: Discussionmentioning
confidence: 97%
“…In the referred work by Gallagher and Vigraham [6], a five neuron CTRNN had been used for suppressing TA instability in a simulated combustion chamber. Our early experiments suggested that a 5 neuron CTRNN was not sufficient for suppressing TA instability in this analog circuit.…”
Section: Ctrnn : Experimental Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been previously demonstrated as effective control devices for 1. Suppressing Thermoacoustic (TA) instability in simulated jet engines [1]. 2.…”
Section: Introductionmentioning
confidence: 99%